Work-family-conflict and family-work-conflict as correlates of job performance among working mothers: implications for industrial social workers (2017)
There has been an increased concern over the inter-role conflict that employees are experiencing as they try to balance the demands of work and family roles since these conflicts could result in negative consequences like poor job performance. Therefore, this study looks at the correlation between work-family-conflict, family-work-conflict and job performance of working mothers. The descriptive survey research design was used for the study. The population of the study comprised all working mothers in public hospital (nurses) and Local Government (clerical staff) in Ekiti State of Nigeria. Purposive and random sampling techniques were used to select three hundred respondents. The major instrument used for this study was a questionnaire tagged “Work-Family Conflict, Family-Work Conflict and Job Performance Questionnaire - WFCFWCAJPQ” adopted from Netemeyer et al. (1996) with 0.85 reliability coefficient. Data collected was analysed with mean, standard deviation and Pearson Product Moment Correlation. Findings showed that work-family-conflict was more predominant with working mother than the family-work-conflict. There was positive significant relationship between work-family-conflict; family work-conflict and job performance of working mothers It was then recommended that Industrial Social Workers should educate working mothers on how to balance their work and family responsibilities in order to have sense of belongingness in both domains and perform efficiently and effectively in the workplace.